Better drugs for Lyme disease: focus on the spirochete - Stricker, Raphael B (Infect Drug Resist, 2018)
Twenty-five years ago, the AIDS epidemic was wreaking havoc around the world. Although “HIV denialists” threatened to undermine research efforts to combat the epidemic, development of targeted antiviral therapy eventually provided effective treatment for the disease. Now the Lyme disease epidemic is wreaking havoc around the world, and “Lyme denialists” are undermining efforts to combat the epidemic. Drawing on our experience with the AIDS epidemic, there is a significant need to develop targeted therapy to control the Lyme disease epidemic.